KERJASAMA KEAMANAN INDONESIA – FILIPINA DALAM MENGATASI MASALAH TERORISME TAHUN 2005-2011 - Adisty Larasati; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The purpose of this research is to understand why are Indonesia and Philippines want to cooperate about security and terrorism in 2005-2011. Indonesia and Philippines are two countries who had so many incidents from the action of terrorism, and both countries had same unstable condition who make the both countries susceptible to issues of terrorism. In this research will be explained too about what are the factors that make these two countries cooperate in tackling terrorism. It is also explained about there are some links between Jemaah Islamiyah and the MILF who became the one of very strong supporting factor for the two countries to cooperate in tackling terrorism. Last thing to be discussed in this research is the international law who the both countries made for this security cooperation in tackling terrorism.This research theoretically has built with neoliberalism perspectives on International Relations and supported by International Cooperation, and International Security theories, and also the concept of non-traditional security. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Technique in this research is through by the study of library. Data which is gotten and collected through the journal books, the last thesis and then from internet has related to the problems.In this research, factors that influences Indonesia and Philippines to cooperate about security and terrorism in 2005-2011 is the strong connection who bond group of terrorist in Indonesia and group of terrorist in Philippines. With this cooperation who made by the both of countries, hopefully can makes that strong connection between the group terrorist of the both countries can gone and the both countries can make a stability in the region of the Southeast Asia.Keywords : Terrorism, Indonesia, Philippines, Security, Cooperation